Rekayasa Perangkat Lunak Performance Indicator dalam Penentuan Penilaian Karyawan dengan Metode Simple Additive Weighting - Yansen, Yansen; Fauziah, Zifa; Ananda, Yesica Wisda; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Employee appraisal is an important factor in the development of a company effectively and efficiently because employee appraisal is one of many indicators in measuring the background of human resources system in the company. Determining the right indicators of human resources can motivate better employee performance. To support this kind of system, a software engineering with Performance Indicator system is needed and data collection techniques by direct observation and data documentation are needed. Application of engineering Key Performance Indicator software for employee performance appraisal using the Simple Additive Weighting method can result in the efficiency of the assessment process in determining the quality of an employee's performance. as well as assisting employees in knowing the results of performance evaluation, and making it easier for supervisors to obtain reports on sales performance ratings so that superiors can and make determine the amount of salary, commision and bonus increases more precisely and efficiently.